Perancangan Mesin Pembuat Pellet Untuk Campuran Cangkang Telur Sebagai Konsentrat Kapasitas 10 Kg/Jam Dengan Metode Pahl dan Beitz - Yudhi Chandra Dwiaji (Journal of Applied Mechanical Engineering and Renewable Energy, 2022)
The egg shell is one of the wasted that is often found in the community and the egg processing industry. With the increase in population and public consumption. Egg shells are generally just thrown away. The content of egg shells in the form of CaCO3, which is harmful to the environment due to microbial activity in the environment, can cause environmental pollution. The use of egg shells as animal feed ingredients and organic fertilizers can be given because egg shells contain several mineral substances such as macro minerals, macro. Machines on the market only produce one form in one process, namely in the form of pellets or flour. In pellet-producing machines on the market, shell waste before being processed, eggs are crushed manually so it can take a lot of time is designing a pellet making machine using the Pahl and Beitz design method. The Pahl and Beitz method has 4 important phases, such as planning, product concept design, shape design and detailed design, so that the design carried out can provide the right solution. The pellet making machine designed with a capacity of 10 kg /hour include process eggshell waste into flour with a grinding unit and pellet maker simultaneously.